Refugee entrepreneurship in Malawi: the nexus between social capital and entrepreneurship among refugees in adversity - Msowoya, Richmond (Graduate School of Business (GSB), 2025)
The influx of refugees across the globe and largely confining refugees to refugee camps remains unresolved, complex, and uncertain. The quest for refugees to improve their livelihoods by engaging in entrepreneurship in host countries leads to harsh policies including encampment policies that restrict refugees to camps. Despite these restrictions and tough conditions in camps setups many refugees continue to thrive with entrepreneurship. Thus, the problem being addressed in this thesis is to explore how social capital develops to promote business entrepreneurship amongst refugees living in camps amid adversity in Dzaleka refugee camp in Malawi. The purpose is to comprehend how social capital develops among refugees in adversity to promote entrepreneurship within camps, between camps and host communities, between host countries and home countries despite various impediments imposed on refugees by host governments. I conduct an inductive, qualitative study of 64 participants over a period of three years. Due to biopolitics of encampment (the use of “state and humanitarian power” to control and manage displaced populations with the pretext of creating order of management), I managed to find four entrepreneurship pathways that refugees’ entrepreneurs utilize, namely homophilic networks(connections, affiliations, bonds, or linkages developed among groups or individuals sharing similar characteristics, aspirations, purposes, or intentions), bricolage, diversification, and adapting supply chains around institutional rules. My findings make four key contributions. Firstly, the study contributes towards research on the biopolitics of encampment, which has been under explored in extant literature. Secondly, the study provides insights on homophilic networks and how they promote business entrepreneurship ventures within the camp, and between the camp and host and home and third countries, and the role of social capital development amongst refugees in promoting business ventures. Thirdly, extant literature has not fully unpacked the interplay between intracamp, intercountry and international business entrepreneurship ventures among refugees living in camps, adding importance to the findings here. Finally, this study makes contributes to the literature by giving insights into the linkages refugee entrepreneurs develop to complex supply chains as they develop their business enterprises. My thesis concludes by providing practical contributions, strategies, and future research recommendations.